Playing the scene of religion: Beauvoir and faith - Zoppa, Karen (Equinox Publishing, 2021)
"This book interrogates popular notions of religion by reading it, out of Derrida and Certeau, as a signifier for a situated historical scene, and shows the existential philosophy of Beauvoir as a performance of that scene"--